THE EU – TURKEY MIGRATION DEAL: RESULTS AND PROSPECTS - Viktoriia V. Krapivina (Научно-аналитический вестник Института Европы РАН, 2022)
The article analyzes the results of the EU – Turkey migration deal of 2016, which is an example of successful externalization of the problem of border control and refugee maintain. Comparing the terms of the deal with the result of their implementation after 6 years of operation, the author comes to the conclusion that in fact the effect of the deal is reduced to the fulfillment of two of its necessary requirements – EU’s funding for the needs of Syrian refugees and Turkey’s readiness to ensure their maintenance on its territory. The author investigates possible scenarios of Turkey’s behavior in the context of its dissatisfaction with migration cooperation with the EU. Its interests regarding the implementation of agreements on the visa regime, renewal of the Customs Union and accession to the EU are not respected, and Turkey also is being tested by the deterioration of the domestic political situation. It is noted that the influx of refugees from Ukraine in the spring of 2022 finally displaced issues related to the stay of Syrians in Turkey from the European agenda. The author claims that the deal will maintain its status quo despite the fact that the parties evaluate the effectiveness of the agreement differently. This will be facilitated to a greater extent by the readiness of the European Union to continue financing the activity of the EU Facility for Refugees in Turkey, Ankara’s failed attempt to put pressure on Brussels earlier and the unwillingness of most Syrians to return to their homeland.